A Philosophical Dictionary, Volume 08 - Voltaire, 1694-1778; Leigh, Oliver Herbrand Gordon; Morley, John, 1838-1923; Smollett, T. (Tobias), 1721-1771; Fleming, William F. (Salt Lake City, UT : Project Gutenberg, 2011)
"A Philosophical Dictionary, Volume 08" by Voltaire is an encyclopedic dictionary published in 1764. This alphabetically arranged work criticizes religious institutions including the Roman Catholic Church, Judaism, and Islam, while advocating for tolerance and freedom of press. Born from a dinner party challenge at Frederick II's court, Voltaire created an affordable, pocket-sized text that educated and provoked simultaneously. Though the public embraced it enthusiastically, religious authorities condemned the work, burning copies in town squares across Europe. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Dictionnaire_philosophique
Release date is 2011-03-28
Produced by Andrea Ball, Christine Bell & Marc D'Hooghe (From images generously made available by the Internet Archive.)
Keywords: Philosophy -- Dictionaries; Criticism (Philosophy)